2019
DOI: 10.4049/jimmunol.1800782
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Upregulated Mitochondria Mass through the SMAD2/3→C/EBPβ→PRMT1 Signal Pathway in Primary Human Lung Fibroblasts

Abstract: Tissue remodeling of subepithelial mesenchymal cells is a major pathologic condition of chronic obstructive pulmonary disease and asthma. Fibroblasts contribute to fibrotic events and inflammation in both airway diseases. Recent mechanistic studies established a link between mitochondrial dysfunction or aberrant biogenesis leading to tissue remodeling of the airway wall in asthma. Protein arginine methyltransferase-1 (PRMT1) participated in airway wall remodeling in pulmonary inflammation. This study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 53 publications
0
59
0
Order By: Relevance
“…However, there are many other ways in TGFβ can modulate mitochondrial activities. TGFβ was reported to increase mitochondrial mass in primary human lung fibroblasts (82). In this study, TGFβ signaling via the canonical pathway culminated in the upregulation of PGC-1α expression.…”
Section: Tgfβ and Mitochondrial Structure And Functionmentioning
confidence: 57%
“…However, there are many other ways in TGFβ can modulate mitochondrial activities. TGFβ was reported to increase mitochondrial mass in primary human lung fibroblasts (82). In this study, TGFβ signaling via the canonical pathway culminated in the upregulation of PGC-1α expression.…”
Section: Tgfβ and Mitochondrial Structure And Functionmentioning
confidence: 57%
“…Available evidence suggests that hypoxia-induced expression of connective tissue growth factor (CTGF), resulting in pulmonary fibrosis, was dependent on C/EBPβ activation [17]. Besides, a previous study confirmed that C/EBPβ was a key mediator of TGF-β-dependent fibroblast remodelling in asthma [25]. Similarly, C/EBPβ may play a pivotal role in the development of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 95%
“…C/EBP-β also participates in the fibrosis of many organs, such as liver, 50 kidney, 30,39,54 and lung. 55 Especially, C/EBP-β can inhibit the progress of renal fibrosis. For example, C/EBP-β reduced fibronectin synthesis by regulating the transcription of TINag while the deficiency of C/EBP-β aggravated renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%